Suplementación con micronutrientes en pacientes con cirugía de bypass gástrico: Estudio prospectivo sobre la inflamación y el metabolismo del hierro en mujeres premenopáusicas - Marin, Flávia Andréia [UNESP]; Verlengia, Rozangela; Crisp, Alex Harley [UNESP]; Novais, Patrícia Fátima Sousa [UNESP]; Rasera-Junior, Irineu [UNESP]; de Oliveira, Maria Rita Marques [UNESP] (ARAN Ediciones, 2017)
Background: Low-grade chronic inflammation in morbid obesity is associated with impaired iron metabolism. Bariatric surgery is effective in weight loss; however, it can induce specific nutritional deficiencies, such as iron, especially in premenopausal women. Alternatively, after surgery, there is an improvement in systemic inflammation, raising questions concerning the dosages of micronutrient supplementation. Objectives: This study aimed to assess the effect of two micronutrient supplementation schemes before and 6 months after a Roux-en-Y gastric bypass (RYGB) surgery on inflammation and iron metabolism in premenopausal women. Methods: This prospective study included 45 premenopausal women (aged 20-45 years; body mass index [BMI] = 35 kg/m2) divided into two supplementation schemes: group 1 (n = 34): daily supplemental dose of 1 RDA 30 days before surgery and 2 RDAs during the six months following surgery; and group 2 (n = 11): daily supplementation of 1 RDA during the 6 months postsurgery. Anthropometry, dietary intake, inflammation, and iron metabolism were monitored. Results: Evident reductions in BMI, high-sensitivity C-reactive protein, and ferritin levels for both groups occurred 6 months after surgery. Additionally, anemia was 9% in both groups after surgery. However, group 1 exhibited an increased transferrin saturation index and reduced transferrin levels. Multivariate regression analysis suggested serum iron, hepcidin, and iron intake determined ferritin values before and after RYGB surgery. Conclusion: Six months after RYGB, systemic inflammation was reduced in both supplementation schemes. However, supplementation of 1 RDA before and 2 RDAs after surgery resulted in better improvements on iron metabolism.
Micronutrient supplementation in gastric bypass surgery: Prospective study on inflammation and iron metabolism in premenopausal women
Keywords: Bariatric surgery; Inflammation; Iron; Micronutrient supplementation; Obesity